2020
DOI: 10.1192/j.eurpsy.2019.9
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use and nonuse in patients with first-episode psychosis: A systematic review and meta-analysis of studies comparing neurocognitive functioning

Abstract: Background. The implications of cannabis use in the onset of early psychosis and the severity of psychotic symptoms have resulted in a proliferation of studies on this issue. However, few have examined the effects of cannabis use on the cognitive symptoms of psychosis (i.e., neurocognitive functioning) in patients with first-episode psychosis (FEP). This systematic review and meta-analysis aim to assess the neurocognitive functioning of cannabis users (CU) and nonusers (NU) with FEP. Methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…differences in neurocognitive performance between patients with and without cannabis use (77). It is important to interpret these results with caution.…”
Section: Comorbidity With Psychosis-spectrum Disordersmentioning
confidence: 93%
See 1 more Smart Citation
“…differences in neurocognitive performance between patients with and without cannabis use (77). It is important to interpret these results with caution.…”
Section: Comorbidity With Psychosis-spectrum Disordersmentioning
confidence: 93%
“…To the contrary, two meta-analyses concluded that cannabis-using psychosis patients exhibited superior (small-to-moderate effects) cognitive functioning for attention, executive functions, working memory, delayed memory, verbal fluency, and visuo-spatial abilities relative to non-using patients ( 75 , 76 ). A further meta-analysis of first-episode psychosis patients did not observe significant differences in neurocognitive performance between patients with and without cannabis use ( 77 ). It is important to interpret these results with caution.…”
Section: Residual Effectsmentioning
confidence: 96%
“…However, among people with schizophrenia, some studies have reported that cannabis users show better cognitive performance than patients who are non-users [127,128]. This finding appears counter-intuitive, as cannabis use in healthy volunteers and other studies in schizophrenia has been associated with impairments in cognitive function [125,129,130]. The association with better performance in schizophrenia may depend on the pattern of cannabis use, as it is mainly evident in infrequent users rather than in regular or dependent users (Chester et al, in submission).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In particular, patients with severe mental disorders have very poor physical health, suffering from coronary heart diseases, diabetes, respiratory, renal, and infectious diseases (13)(14)(15)(16)(17). The higher presence of physical illnesses compared to the general population is due to several causes (18,19), including the adoption of unhealthy lifestyle behaviors, such as heavy smoking (20)(21)(22)(23), heavy alcohol drinking (24)(25)(26), use of illicit drugs (27,28), unbalanced diet and low levels of physical activity (29).…”
Section: Introductionmentioning
confidence: 99%